PERLINDUNGAN HUKUM TERHADAP BARANG PENUMPANG DI BAGASI PESAWAT TERBANG DALAM RANGKA MEWUJUDKAN KETAHANAN NASIONAL - Sri Wahyuni; Esther Masri (Jurnal Hukum dan Bisnis (Selisik), 2021)
This research is motivated by the occurrence of several cases of lost items in aircraft luggagewhich have caused losses and have an impact on the trust of the Indonesian people and theinternational community in the security of the Indonesian aviation industry. This study aims todetermine how the legal protection of passenger items in aircraft baggage in order to achievenational resilience. Regarding the concept of national resilience, it is a dynamic condition of anation that contains resilience in facing challenges that can endanger the integrity of theIndonesian nation's survival based on the principle of national resilience and the provisions ofLaw Number 8 of 1999 concerning Consumer Protection and Aviation Law. The researchmethod used is a normative legal research method, thus this study will analyze cases of lostitems in aircraft baggage in accordance with applicable laws and regulations. Based on theresults of research and analysis, it can be concluded that the legal protection of passenger goodsdivided by aircraft has not been fulfilled properly, especially regarding the amount ofcompensation value, this is an important point for providing solutions to create security andpublic trust in the aviation industry in order to achieve national resilience